Hygrothermal Properties Analysis of Bamboo Building Envelope with Different Insulation Systems in Five Climate Zones - Hongping Li; Shiyu Yang; Ziqiong Zha; Benhua Fei; Xiaohuan Wang (Buildings, 2023)
Laminated bamboo lumber (BLL) and bamboo scrimber (BS) are potential environmentally friendly building materials, considering that they are hygroscopic materials and that their hygrothermal performance is closely related to the occupants’ comfort, their building durability, and building energy consumption. This study carried out material property tests on bamboo-based materials (BLL and BS) and analyzed hygrothermal performance simulations on bamboo exterior wall constructions in five major climatic zones using WUFI. Results show that BS had a greater heat storage capacity than BLL. However, BLL showed a relatively higher moisture sorption capacity, and BLL was more easily permeated by vapor than BS. The water content (WC) of 12 walls of BLL and BS was below 20%. BLL and BS met the requirements of the envelope, and the WC of BS was lower than that of BLL. Based on the results, the walls designed in this study are suitable for the corresponding climate zones. In the cold and severe climate zones especially, the external insulation system walls performed better than the internal insulation system. The external insulation system was recommended for these two climate zones. The design and simulation results of walls made of two types of bamboo-based materials provide a scientific basis for the application of the material.